1996
DOI: 10.1136/jmg.33.9.731
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards cancer predictive testing and transmission of information to the family.

Abstract: Material and methods POPULATION SAMPLEThe six participating regional cancer centres were selected with a view to giving a representative picture of the French population as a whole (south: Marseille, Toulouse; north: Lille; west: Nantes; centre: Paris/St Cloud, Clermont-Ferrand) and covered a total population of more than 4 million inhabitants. The main criterion used for inclusion in the study was the presence of breast cancer running in the family, either in the patient or in at least one first degree relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 27 publications
4
58
0
3
Order By: Relevance
“…This supports previous data that suggest that, despite counseling efforts, mutation carriers describe decreased disclosure to relatives with whom affected individuals have difficult or distant relationships (Julian-Reynier et at., 1996;Green et al, 1997;Hughes et al, 2002;Forrest et al, 2003;McGivem et al, 2004), or with whom there is an FDR available to discuss positive family results (Claes et al, 2003;Peterson et al, 2003;McGivern et al, 2004). In this family context, it is concerning that a person several times removed from the actual genetic counseling process provides genetic risk information to other family members, potentially distorting the content of the transmitted information.…”
Section: Discussionsupporting
confidence: 90%
“…This supports previous data that suggest that, despite counseling efforts, mutation carriers describe decreased disclosure to relatives with whom affected individuals have difficult or distant relationships (Julian-Reynier et at., 1996;Green et al, 1997;Hughes et al, 2002;Forrest et al, 2003;McGivem et al, 2004), or with whom there is an FDR available to discuss positive family results (Claes et al, 2003;Peterson et al, 2003;McGivern et al, 2004). In this family context, it is concerning that a person several times removed from the actual genetic counseling process provides genetic risk information to other family members, potentially distorting the content of the transmitted information.…”
Section: Discussionsupporting
confidence: 90%
“…Before the availability of clinical testing, various studies in breast carcinoma patients, 14 healthy family members of breast or ovarian carcinoma patients, 8 -12 and the general population [13][14][15][16] have reported high level of interest in BRCA1/2 genetic testing, ranging from 69% to 96%. 8,9,[11][12][13][14]16,30,31 Since genetic testing for BRCA1/2 became available, there have been few published studies on the actual utilization of testing in clinical practice. 18 Only one-quarter of patients who were eligible to consider testing in our clinical population eventually were tested or arranged to have an affected family member tested.…”
Section: Discussionmentioning
confidence: 99%
“…Julian-Reynier et al 57 reported that about 14% of 161 patients who had been asked to contact their relatives, firmly refused to do so, mainly because of problematic familial relationships. Other significant barriers to informing family members are guilt, shame, anxiety or depression.…”
Section: Decision Counsellingmentioning
confidence: 99%